Baicalin Inhibits NOD-Like Receptor Family, Pyrin Containing Domain 3 Inflammasome Activation in Murine Macrophages by Augmenting Protein Kinase A Signaling - Li, Chen-Guang; Yan, Liang; Mai, Feng-Yi; Shi, Zi-Jian; Xu, Li-Hui; Jing, Yan-Yun; Zha, Qing-Bing; Ouyang, Dong-Yun; He, Xian-Hui (Frontiers in Immunology, 2017)
The ﬂavonoid baicalin has been reported to possess potent anti-inflammatory activities by suppressing inflammatory signaling pathways. However, whether baicalin can suppress the activation of NOD-like receptor (NLR) family, pyrin containing domain 3 (NLRP3) inflammasome in macrophages is largely unknown. Here we showed that baicalin treatment dose-dependently inhibited ATP or nigericin-induced NLRP3 inflammasome activation, as revealed by the decreased release of mature interleukin (IL)-1β, active caspase-1p10, and high mobility group box-1 protein (HMGB1) from lipopolysaccharide (LPS)-primed bone marrow-derived macrophages. The formation of ASC specks, a critical marker of NLRP3 inflammasome assembly, was robustly inhibited by baicalin in the macrophages upon ATP or nigericin stimulation. All these inhibitory effects of baicalin could be partly reversed by MDL12330A or H89, both of which are inhibitors of the protein kinase A (PKA) signaling pathway. Consistent with this, baicalin strongly enhanced PKA-mediated phosphorylation of NLRP3, which has been suggested to prevent ASC recruitment into the inflammasome. Of note, the PKA inhibitor H89 could block baicalin-induced NLRP3 phosphorylation on PKA-specific sites, further supporting PKA’s role in this process. In addition, we showed that when administered pre and post exposure to E. coli infection baicalin treatment significantly improved mouse survival in bacterial sepsis. Baicalin administration also significantly reduced IL-1β levels in the sera of bacterial infected mice. Altogether, our results revealed that baicalin inhibited NLRP3 inﬂammasome activation at least partly through augmenting PKA signaling, highlighting its therapeutic potential for the treatment of NLRP3-related inflammatory diseases.